0396 A Randomized, Double-Blind, Placebo-Controlled Trial of A Natural Polyphenol Blend on Sleep and Daytime Functioning in Adults with Sleep Complaints but Not Sleep Disorders. (12th April 2019) - Grandner, Michael A; Warlick, Chloe; Gehrels, Jo-Ann; Sanchez, Christopher; Alfonso-Miller, Pamela
Abstract: Introduction: Sleep complaints, such as occasional sleeplessness and feeling unrefreshed, are common. Few safe, empirically-supported interventions for these complaints exist because most studies focus on disorders. This study examined effects of a natural ingredient on sleep-related outcomes in non-sleep-disordered adults. Methods: N=100 adults with sleep complaints but not sleep disorders were randomized to receive either a proprietary polyphenol blend of a spearmint/green-tea extract, or placebo for 30 days, 30 minutes before bed. Participants completed sleep diaries (including morning ratings of "refreshed" [1-10 scale] and Karolinska Sleepiness Scale), wore a Fitbit sleep/activity monitor, completed Insomnia Severity Index (ISI) and Pittsburgh Sleep Quality Index (PSQI), and completed a JoggleResearch cognitive battery before and after the 30-day intervention. Preliminary analyses examined within-group change in sleep duration and morning refreshed/sleepiness, and between-group analyses examined change in ISI score and whether PSQI category (cutoff=5pts) changed during the study, adjusted for age, sex, and mood change. Results: Preliminary per-protocol analysis (N=93, mean age=31, range=22-50y, 62% female) of within-group changes from baseline showed that objective sleep duration increased in the treatment (Δ=27.8min, 95%CI[9.5, 46.0], p=0.0038) but not the control group (Δ=9.0min, 95%CI[-15.9, 33.9], p=0.47), and subjective sleep duration increased in both the treatment (Δ=39.6min, 95%CI[9.7, 69.6], p=0.01) and control (Δ=34.3min, 95%CI[8.4, 60.2], p=0.01) groups. Daytime "refreshed" ratings were improved in both the treatment (Δ=1.4, 95%CI[0.7, 2.1], p=0.0003) and control (Δ=1.0, 95%CI[0.4, 1.6], p=0.002) groups, but reductions in sleepiness were seen only in the treatment group (Δ=0.8, 95%CI[0.3, 1.4], p=0.005) and not the control group (Δ=0.4, 95%CI[-0.1, 1.0], p=0.13). In between-group comparisons, the treatment group had greater improvements in ISI score (Δdiff=2.15pts, 95%CI[0.43, 3.87], p=0.01). Also, in examining PSQI category change, the treatment group was less likely than the control group to transition to poor sleep (RRR=0.16, 95%CI[0.04, 0.63], p=0.009). In cognitive measures, within-group improvements were seen in tests of processing speed, working memory, and executive function. Additional analyses (including cognitive details) are forthcoming. Conclusion: Despite evident placebo effects, the treatment group overall demonstrated improvements in nighttime and daytime sleep-related variables, as well as cognitive function. Support (If Any): Supported by Kemin Foods, LC